Chover-Type Laws of the Iterated Logarithm for Continuous Time Random Walks - Kyo-Shin Hwang; Wensheng Wang (Journal of Applied Mathematics)
A continuous time random walk is a random walk subordinated to a renewal process used in physics to model anomalous diffusion. In this paper, we establish Chover-type laws of the iterated logarithm for continuous time random walks with jumps and waiting times in the domains of attraction of stable laws.